THE INFLUENCE OF EXTRINSIC REWARD AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE (CASE STUDY AT PT. ASTRA INTERNATIONAL DAIHATSU, MANADO) - Trivena, Koroh Lavenia; Kindangen, Paulus; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The lack of resources for a character will affect someone in association or in a performance. Therefore, in a strong mental strive for the development of a person. Because when someone does have a strong character things like that will be appreciated by the leadership in it. It can solidify the progress of a personâ€™s performance that will affect the company. So it can generate quality employees instead of the usual course. Needs quality employees is very important in the company. Because of where the company will use all means the maintain of a qualified employees who can dedicates their loyalties to the company. The existence of reciprocity, either from the company or the employee. Improved performance of employees will bring progress for the company to be able to survive in an unstable competitive business environment. Therefore, efforts to improve the performance of employees is the most serious management challenges because of the success to achieve the goals and the survival of the company depends on the quality of performance of human resources in it.Â Keywords: Extrinsic Reward, Leadership style, and Employee Performance.